PELATIHAN PENERAPAN MANAJEMEN PENJAMINAN MUTU PENDIDIKAN DALAM PROSES PEMBELAJARAN MELALUI METODE BLENDED LEARNING DI KARAWANG - Bambang Ismaya; Astuti Darmiyanti; Abduloh Abduloh; Ayu Amelia; Selis Selis (Universitas Muhammadiyah Manado, 2022)
This training is that the management process for process standards has not been optimally implemented properly, and the standard management of educators and educational staff has not been maximized including many teachers still not mastering the use of Information Technology (IT) as a means of supporting learning. The purpose of this training is to improve the competence of teachers in the learning process using the blended learning method so that the quality of learning becomes quality. This training was held in Karawang. This training refers to the standard of education management which has become the stipulation of the National Education Standards Agency (BSNP) so that it reflects superior and competitive management standards. Implementation of the training through the management program for the utilization of educators and education personnel, namely through workshops, in-house training, trainings, implementation of a clear reward and punishment system for teachers, education personnel and students. Supervision and evaluation of education quality management in the learning process through the blended learning method in Karawang is related to inputs such as infrastructure, students, teaching staff, financing and others that are not in accordance with the standards expected to achieve quality education. The result of this training is how a teacher is able to carry out the learning process using the blended learning method, which is a combination of online and offline learning so as to be able to achieve quality education outcomes